A liquid biopsy for head and neck cancers. (1st February 2016) - Schmidt, Henri; Kulasinghe, Arutha; Perry, Chris; Nelson, Colleen; Punyadeera, Chamindie
ABSTRACT: Head and neck cancer patients often present with advanced metastatic disease resulting in a poor 5-year survival. Therefore, there is a need for non-invasive diagnostic tools that could complement conventional imaging to inform clinicians of patient outcomes and treatment responses. A liquid biopsy addresses this unmet clinical need; a simple peripheral blood draw could provide information about the disseminated disease in terms of circulating tumor cells and circulating tumor DNA. Moreover, detectable tumor DNA in the saliva of head and neck cancer patients could signify the early signs of the disease and present an opportunity for clinical intervention. This review provides an overview of the current literature with regard to the feasibility of such a test in the head and neck cancer field and highlights the need for such a test.